Studi Kelayakan Ekonomis Rencana Pembangunan Pelabuhan Sungai Liong Desa Berancah Kabupaten Bengkalis - Nur Rahmani; Akmal Lazuardy (Ekonomis: Journal of Economics and Business, 2019)
The fish shelter port (TPI) is a need that needs to be prepared by local village officials and the government for every coastal village in Bengkalis Regency. This research was conducted in the Berancah village of Bantan District. The analysis in this study describes the economic feasibility mathematically for the construction of a fish storage port (TPI) by calculating the cost ratio (B / C ratio) benefit analysis, payback period (PP), net present value (NPV), and internal rate of return ( IRR). The results obtained from the NPV value (3,661,267,645), BCR value (0.943), IRR value of 10.01%, and PP are in the period of 30 years. Taken as a whole by standardizing the calculations, it can be concluded that the planned construction of a fish shelter in Berancah village is considered not economically feasible, but economic analysis is not merely a benchmark for feasibility, reviewed for the future many benefits will be received by the community around the location of the development plan so that it can improve the welfare of the community in Berancah village.